2020
DOI: 10.1128/aac.01463-20
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Profile and Characterization of the Hepatitis B Virus Core Protein Inhibitor ABI-H0731

Abstract: ABI-H0731, a first-generation Hepatitis B Virus (HBV) core protein inhibitor, has demonstrated effective antiviral activity in chronic hepatitis B (CHB) patients in a Phase 1b clinical trial and is currently being further evaluated in Phase 2 clinical trials. Here, we report the preclinical profile of ABI-H0731. In in vitro cell culture systems (HepG2 derived cell lines: HepAD38 and HepG2-NTCP and Primary Human Hepatocyte (PHH)), ABI-H0731 exhibited selective inhibition of HBV DNA replication (EC50 from 173 nM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Not surprisingly, many of the CpAM-resistant Cp mutations severely compromised pgRNA encapsidation and viral DNA synthesis [32,54,60] (Fig 1). Moreover, while single amino acid mutations at the HAP pocket usually confer resistance to selected chemotypes of CpAMs [20,32,60,61], our systematic mutagenesis study of 25 amino acid residues at the wall of HAP pocket identified that several mutations of residue P25, T33 or I105 conferred strong resistance to the inhibition of HBV DNA replication by heteroaryldihydropyrimidines (HAP) as well as four chemotypes of type II CpAMs [26]. Importantly, seven out of the nine mutations supported relatively high levels of pgRNA packaging and DNA synthesis, which allowed investigating the role and mechanism of these residues in other steps of viral replication.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Not surprisingly, many of the CpAM-resistant Cp mutations severely compromised pgRNA encapsidation and viral DNA synthesis [32,54,60] (Fig 1). Moreover, while single amino acid mutations at the HAP pocket usually confer resistance to selected chemotypes of CpAMs [20,32,60,61], our systematic mutagenesis study of 25 amino acid residues at the wall of HAP pocket identified that several mutations of residue P25, T33 or I105 conferred strong resistance to the inhibition of HBV DNA replication by heteroaryldihydropyrimidines (HAP) as well as four chemotypes of type II CpAMs [26]. Importantly, seven out of the nine mutations supported relatively high levels of pgRNA packaging and DNA synthesis, which allowed investigating the role and mechanism of these residues in other steps of viral replication.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…ABI-H0731 marked the beginning of a new category of compounds. It is a dibenzo-thiazepine-2-carboxamide derivative, and it has been shown to cause a significant reduction in HBV DNA and RNA levels in phase I clinical trials, as a core protein modulator [ 39 , 205 ].…”
Section: Novel Therapeutic Strategiesmentioning
confidence: 99%
“…Interference with capsid assembly and inhibition of pgRNA encapsidation (the so‐called primary mechanism) is the most important instrument of inhibition. An additive check on HBV replication has been shown on ultra‐sensitive HBV DNA tests 27 by the turnover of cccDNA and by the monitoring of emergence of signature mutations 28 . A reduction in pgRNA encapsidation is shown by a reduction in particles containing HBV RNA.…”
Section: Inhibitors Of Hbv Replicationmentioning
confidence: 99%